Culture Shock in The Boardroom: Managing Cross-Cultural Business Interactions in Sub-Saharan Africa - Oyasor, Emmanuel (Management Institute Faculty of Economics Universitas Andalas, 2025)
Culture shock among executive leadership teams has become a growing challenge in Sub-Saharan African boardrooms, largely due to the increasing frequency of cross-cultural interactions. This study investigates how cultural intelligence, cross-cultural training, and leadership style influence the occurrence of culture shock in multinational corporate governance. Drawing on Cultural Intelligence Theory and Transformational Leadership Theory, a quantitative cross-sectional design was employed using secondary data from 312 firms across Nigeria, Kenya, Ghana, and South Africa. Firm level archival data were analyzed using Pearson correlation and multiple regression analysis in STATA version 26. The results reveal a significant negative relationship between each of the three variables and culture shock: cultural intelligence cross cultural training, and leadership style. These findings suggest that firms with stronger cultural competence, structured training, and inclusive leadership are better equipped to reduce disorientation and interpersonal tension in diverse board settings. The study recommends that organizations institutionalize cultural intelligence frameworks, formalize cross-cultural training programs, and promote transformational leadership practices to improve boardroom cohesion and strategic effectiveness.